On the Optimal Capital Tax Rate in Overlapping Generations Models with Capital - Skill Complementarity - Burkhard Heer (CESifo GmbH, 2025)
The optimal capital income tax rate has been shown to be nonzero in overlapping generations (OLG) models, as it helps redistribute income between cohorts and individuals with different labor supply elasticities and individual productivities. We show in a medium-scale OLG model that the optimal capital income tax rate is highly sensitive to the assumption of capital-skill complementarity in production technology. The imposition of the production function of Krusell et al. (2000) rather than the standard Cobb - Douglas function increases the optimal capital tax from 9.2% to 27.3% in our benchmark model. We also study the sensitivity of this result in the context of an aging economy and find that the optimal capital income tax increases over the upcoming decades depending on possible pension reforms and debt policies.
Keywords: E13; H21; H24; H25; 330; capital income taxes; Chamley-Judd result; skill-biased technological change; demographic change.